2021
DOI: 10.3389/fmicb.2021.624980
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Viral Infection Rates and Cell Sizes of Infected Prokaryotes in a Large and Deep Freshwater Lake (Lake Biwa, Japan)

Abstract: As viruses regulate prokaryotic abundance and the carbon cycle by infecting and lysing their prokaryotic hosts, the volume of infected prokaryotes is an important parameter for understanding the impact of viruses on aquatic environments. However, literature regarding the seasonal and spatial variations in the cell volume of infected prokaryotes is limited, despite the volume of the prokaryotic community varying dynamically with season and water column depth. Here, we conducted a field survey for two annual cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
5
11
1
1
Order By: Relevance
“…We principally focused on lytic viruses, which through the rapid production of viral particles directly contribute to viral shunt rather than dormant temperate viruses. Viral lytic infection determined by the FVIC approach through direct observation using TEM in Lake Goule (1.2 to 3.7%) was comparable and within the typical range of those (i.e., <5%) reported for freshwater environments [7,41,46]. In contrast to reports from other freshwater systems, the absence of a relationship between the percentage of viral-infected cells and both viral and bacterial abundances indicates that the viral attack was dependent on the density of the susceptible community, rather than the density of the total host population.…”
Section: Standing Stock and Lytic Infectionsupporting
confidence: 68%
See 1 more Smart Citation
“…We principally focused on lytic viruses, which through the rapid production of viral particles directly contribute to viral shunt rather than dormant temperate viruses. Viral lytic infection determined by the FVIC approach through direct observation using TEM in Lake Goule (1.2 to 3.7%) was comparable and within the typical range of those (i.e., <5%) reported for freshwater environments [7,41,46]. In contrast to reports from other freshwater systems, the absence of a relationship between the percentage of viral-infected cells and both viral and bacterial abundances indicates that the viral attack was dependent on the density of the susceptible community, rather than the density of the total host population.…”
Section: Standing Stock and Lytic Infectionsupporting
confidence: 68%
“…Flow cytometry signatures of viral and bacterial abundances revealed that their counts were within the reported range of values for mesotrophic freshwater systems [39][40][41], with no marked fluctuation in their ratio with time and space. Irrespective of the sampled depths, viral abundance was better described by a power law function of bacterial abundance with a scaling exponent less than 1, unlike reports from other freshwater systems [7,42] indicating that viral abundance increases less than proportionately given increases in bacterial abundances as previously reported for nutrient limited systems [43].…”
Section: Standing Stock and Lytic Infectionsupporting
confidence: 58%
“…The first was comprehensive metagenomic sampling in an ecosystem. We targeted freshwater bacterioplankton assemblages sampled spatiotemporally (2 depths × 12 months) at a pelagic station on Lake Biwa, a monomictic lake with an oxygenated hypolimnion that harbors one of the best-studied freshwater microbial ecosystems (12)(13)(14)(15)(16). The second step was long-read metagenomic assembly, which can overcome the problem of fragmented assembly using reads longer than a repeat or hypervariable region (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The first was comprehensive metagenomic sampling in an ecosystem. We targeted freshwater bacterioplankton assemblages sampled spatiotemporally (2 depths  12 months) at a pelagic station on Lake Biwa, a monomictic lake with an oxygenated hypolimnion that harbors one of the best-studied freshwater microbial ecosystems (12)(13)(14)(15)(16). The second step was long-read metagenomic assembly, which can overcome the problem of fragmented assembly by using reads longer than a repeat or hypervariable region (17)(18)(19)(20).…”
mentioning
confidence: 99%